LOCAL COMMUNITY PARTICIPATION MANIFESTS SUSTAINABLE TOURISM IN THE BATUR GEOPARK TOURISM AREA - I Gede Wiramatika; Dewa Ayu Suryawati (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
Batur as a tourism area recognized by UNESCO with its very unique location. Batur as one part of the Batur Global Geopark is a model of sustainable tourism planning and development in supporting the preservation of culture, natural environment, local communities, economy, and standard of living. Good planning and development will be able to produce a good strategy in developing existing tourism resources. This study aims to further examine the participation of local communities in the management of Batur Village as a tourist destination in Kintamani, regarding local community participation in the development of the Batur Geopark tourist area, obstacles faced by local communities in the development of the Batur Geopark tourist area, and efforts made by the Government in the development of the Batur Geopark tourist area. This research method is quantitative and qualitative, data collected through interviews, questionnaires, observations, literature studies, documentation studies. The method of determining informants uses key informants whose data comes from people who are considered to know the research object such as, tourism industry entrepreneurs, community leaders, and the community then the data is analyzed using qualitative descriptive data analysis techniques. The presentation of data analysis in this study is done qualitatively through verbal delivery with descriptive interpretative techniques. The results of this study indicate that community participation starting from the planning, implementation, and supervision stages plays a very active role in the development of the Batur Geopark tourism area, and obstacles are still found in the development of the Batur Geopark tourism area in the ongoing mining activities on the slopes of Mount Batur which are not in accordance with the Conservation concept included in the development of the Batur Geopark.